Relationship between anthropometric characteristics and strength in national team lower age categories of windsurfers - Meriç Ödemiş; Özgür Nalbant (Ozlem Book Center, 2023)
The aim of this study was to investigate the relationship between some selected anthropometric variables and strength performance of windsurfers. Twenty-seven windsurfers with an average age of 14.92±1.91, an average height of 168.66±10.56, an average weight of 56.21±8.83 % fat 15.43±6.98, a fat mass of 8.54±4.06 and a BMI of 19.65±1.79 actively competing in the Techno Plus and Techno 293 classes of the Turkish National Team participated in the study. Weight, height, arm-leg, and foot length were measured from anthropometric tests, while handgrip-leg-back strength and standing long jump tests were applied from strength tests. In the study, a significant relationship was observed between back strength and height (r=0.691) and back strength and right handgrip (r=0.644) in female surfers (p<0.005). It was found that there was a significant relationship between right handgrip (r=0.647), left handgrip (r=0.526), back strength (r=0.633), and leg strength (r=0.640) with the standing long jump test of male surfers (p<0,001). At the end of the study, it was determined that there was a relationship between some anthropometric values, which were thought to be effective in the performance of windsurfers, and strength performances. Paying attention to these characteristics in the selection of surfer-specific skills and training programs can be a factor for success.